2015
DOI: 10.1002/jcb.25373
|View full text |Cite
|
Sign up to set email alerts
|

Fyn Accelerates M Phase Progression by Promoting the Assembly of Mitotic Spindle Microtubules

Abstract: The mitotic spindle is the major piece of cellular machinery essential for faithful chromosome segregation. Whereas Fyn, a member of Src-family kinases, is known to be localized to the meiotic and mitotic spindle microtubules, the role of Fyn in mitotic spindle formation has not yet been completely elucidated. In this study, we studied the role of Fyn in spindle formation and effects on M-phase progression. Re-expression of Fyn induced increases in the fluorescence intensity of mitotic spindle microtubules in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 58 publications
1
18
0
Order By: Relevance
“…Triple knockout mutations of c-Src, c-Yes, and Fyn in SYF cells (18) resulted in spindle misorientation, and re-introduction of c-Src rescued it (19). Re-introduction of Fyn into SYF cells facilitates mitotic spindle formation by increasing microtubule polymerization, leading to the acceleration of M-phase progression (20). Based on the role of the Src-family kinases in cell division and the requirement of spatio-temporal regulation of mitotic kinases, we expected that v-Src could disturb cell division because its kinase activity and subcellular localization are deregulated and different from those of c-Src (6).…”
mentioning
confidence: 99%
“…Triple knockout mutations of c-Src, c-Yes, and Fyn in SYF cells (18) resulted in spindle misorientation, and re-introduction of c-Src rescued it (19). Re-introduction of Fyn into SYF cells facilitates mitotic spindle formation by increasing microtubule polymerization, leading to the acceleration of M-phase progression (20). Based on the role of the Src-family kinases in cell division and the requirement of spatio-temporal regulation of mitotic kinases, we expected that v-Src could disturb cell division because its kinase activity and subcellular localization are deregulated and different from those of c-Src (6).…”
mentioning
confidence: 99%
“…We have shown that Src-family tyrosine kinases play important roles in mitosis141826272832. In particular, mitotic activation of c-Src, c-Yes, Lyn and Fyn, which are all co-expressed in HeLa cells, takes place downstream of Cdk1 activation during M phase18.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Src-family kinases have been reported to regulate cell division232425. We then found the roles of Src-family kinases in spindle orientation, spindle assembly, and cytokinesis abscission17262728. Despite the importance of membrane anchorage of Src-family kinases, the role for their lipid modifications in cell division is largely unknown.…”
mentioning
confidence: 96%
“…Each member of the Src family kinases appears to have a distinct role in cell division. Fyn, a member of Src family kinases, participates in the assembly of mitotic spindle microtubules and accelerates mitotic progression [36]. c-Src promotes proper spindle orientation in early prometaphase [37].…”
Section: V-src Suppresses Cell Proliferation and Induces Tetraploimentioning
confidence: 99%